Brahui Poets of the Persian Language - Sarparra, Hafeezullah; Din, Nizam Ud; Younas, Muhammad (sourcecoder, 2024)
The Brahui ethnic group, primarily residing in parts of Pakistan, Iran, and Afghanistan, has historically shared deep-rooted connections with Persian through various domains including historical, social, financial, religious, and literary interactions. Persian served as the official, academic, and secondary religious language for the Muslim Umma, second only to Arabic. Recognized for its cultural richness and literary prestige, Persian was perceived as a language of pride, dignity, and intellectual capability. Consequently, many writers and poets out of Iran also wrote in Persian language. This prestige encouraged many Brahuis to compose poetry in Persian, thereby enriching its literary tradition. The article aims to introduce these Brahui poets, highlighting their pivotal role in promoting Persian language and poetry in their region. Through their works, these poets have not only preserved the linguistic and cultural heritage but also enhanced the literary landscape of Persian poetry.